Socio-economic Aspects of Mortgage Lending for Housing Construction in Tatarstan - Romanova, Anna Ilyinichna; Afanasyeva, Albina Nazipovna; Mavlyautdinov, Almaz Safiullovich; Mukharramova, Regina Ramilevna; Shindina, Tatiana Aleksandrovna (International Journal of Economics and Financial Issues, 2016)
This article describes the problems of regulation of mortgage lending under current economic conditions. Mortgage mechanism of housing acquisition is one of the highest priorities of the market economy system, and allows to create favorable investment climate. One of the key requirements of a long-term mortgage lending system is to ensure the availability of mortgages for people with middle income households. The system of mortgage lending should be of market rather than of subsidized character so that it should be completely transparent and understandable to all participants of the process of mortgage lending. However, the current legal regulation of the mortgage does not allow to solve the problem of meeting the housing construction needs of a large part of the population, particularly of low-income one. Keywords: construction, mortgage, credit, market, housing JEL Classifications: I38, H41